Chalcomer assembly of optical chemosensors for selective Cu2+ and Ni2+ ion recognition1. Issue 17 (27th February 2015) - Singh, Gurjaspreet; Singh, Jandeep; Mangat, Satinderpal Singh; Singh, Jasbhinder; Rani, Sunita
<x xml:space="preserve">Abstract</x> The o-, m- and p-isomeric units of chalconyl triazole-based, caged organosilicon complexes were efficiently synthesized and explored for their cationic chemosensing activities.